Kuat Geser Kayu Laminasi Acacia Crassicarpa Menggunakan Perekat Epoxy - Rani Putri Handayani; Fakhri Fakhri; Alfian Kamaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2022)
Indonesia is a tropical country that has various types of wood. However, the supply of wood time to time is decreasing, while in construction the demand for wood is increasing. This increase has resulted in massive exploitation of the forest, so that the availability of large diameter timber from natural forests is increasingly limited. The use of wood that has a shorter cutting age (10-15 years) and has a small diameter is not efficient as a structural or construction component. The technology used is a structural form that does not come from whole wood but rather a laminated component that is made through a bonding process. This study aims to determine the shear strength of solid testing, solid coating testing, lamination testing, and coating lamination testing. The wood used in this study is acacia crassicarpa wood and the adhesive used is epoxy adhesive. The adhesive weight used was 50 MDGL (Multilayer Double Glue Line). From the test for testing the solid shear strength is 4,01 MPa, the shear strength of the laminate is 2,10 MPa, the shear strength of the solid coating is 3,37 MPa, the shear strength of the coating laminate is 2,83 MPa.Key words: Laminate beam, acacia crassicarpa wood, shear strength, epoxy adhesi.